Will my numbers add up correctly if I round them?. Issue 549 (17th October 2016) - Hopkins, David
Abstract : I recently wrote a solution to a student problem. The answers were the probabilities for four possible outcomes. As a check on the calculations, I wanted to say 'As expected, these probabilities add up to 1.' However, they didn't! Because of rounding, the probabilities (which I was quoting to four decimal places) only added up to 0.9999. To rescue the situation I tried rounding to 3DP or 5DP instead, but these didn't add up correctly either.